Alpha‐gal syndrome: An emerging cause of food and drug allergy. Issue 8 (6th July 2020) - Rutkowski, Krzyszof; Wagner, Annette; Rutkowski, Ryszard; Sowa, Paweł; Pancewicz, Sławomir; Moniuszko‐Malinowska, Anna
Abstract: Alpha‐gal syndrome (AGS) describes a wide spectrum of hypersensitivity reactions mediated by specific IgE to the α‐gal epitope (galactose‐α‐1, 3‐galactose) ubiquitously expressed on glycolipids/glycoproteins of most mammals. This fascinating new entity has completely changed the paradigms of allergy as allergic response is directed against an oligosaccharide and the reactions can be both immediate and delayed. They appear to be stimulated only by tick bites which induce production of α‐gal specific IgE antibodies that lead to (at times fatal) hypersensitivity response. AGS is completely different to previously described anaphylaxis to tick saliva. It provides unique insight into the interplay between different arms of the immune system and the role of ectoparasites in the development of anaphylaxis to food and medication in patients at risk of tick bites including travellers. This review summarises recent advances in our understanding of its clinical presentation, pathomechanism and role of various tick species in the development of AGS.